If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3x + -2 + 1 = -7 Reorder the terms: -2 + 1 + -3x = -7 Combine like terms: -2 + 1 = -1 -1 + -3x = -7 Solving -1 + -3x = -7 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + -3x = -7 + 1 Combine like terms: -1 + 1 = 0 0 + -3x = -7 + 1 -3x = -7 + 1 Combine like terms: -7 + 1 = -6 -3x = -6 Divide each side by '-3'. x = 2 Simplifying x = 2
| -7g=-2-6g | | 12x^2-16x-6=0 | | -7g=-2-6 | | 12k=-36 | | 16-20x-21-6x=18-6x-12x-1 | | -5y+10=-6y | | 23a+7= | | 9v=10v+9 | | 17-6x+3x-5=x+11+4x | | -3m+10=-4m | | 17-6x+3x-5=x+11 | | 6+16x=17x+2 | | 5h=7h+8 | | 24.3=14.4+2a | | 18a-7= | | 6=-5d+11 | | 10x-14-6x=18 | | 2(2x+5)=4 | | 4z-4=10 | | 9x+16=6x+106 | | 10p^2-90p=0 | | x-75x=6x | | 0.5x+0.3=1.2 | | 5(12-x)=25 | | 2x(8x-5)=(5-4x)2 | | 15y^3-123y^2+24y= | | 2x+5+2x=1 | | 7y=-19y+2 | | 15+5(3c-2)= | | -6(8x-3)=-36+6x | | 5(a+4)+3(6a-7)= | | 4x-3=-2x+27 |